W imię Boga Jedynego! (Aleksiej Warłamow „Zatopiona arka”) - Lewandowska, Agnieszka (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to present a religious situation described by Aleksey Varlamov in his novel Zatonuvshiy kovcheg. The spiritual life of Russians after Perestroika not only turned out to be a period of resurgence of Orthodox Christianity, but also the emergence as well as restoration of previously existing sects. Therefore, this novel amounts to a new voice of the discussion on the Russians’ spiritual life then, now and in the future. The author tries to prove that the reawakening of sects brings danger to Russian people, especially to the young generation. This paper presents an analysis of those fragments of the novel that refer to religious subjects and contain descriptions of sects (the Old Believers and the Skoptsy). Besides, spiritual leaders of these sects (Vassian and Luppo) are characterized. The insight into the history of these religious groups is provided and supplemented with Varlamov's descriptions from the novel.